RELIGIOSITY OF MEDIATORS BETWEEN SELF REGULATED LEARNING AND ACADEMIC INTEGRITY - Sarbini, Sarbini; Supriyatin, Tintin; Sukaesih, Esih; Kusnawan, Aep; Bin Yunus, Ahmad Rezelan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The purpose of this study is to determine the effect of self-regulated learning on student academic integrity with religiosity as the moderator variable. The approach used in this research is correlational causality. By using three measurement scales (self-regulated learning scale , academic integrity scale and religiosity) for 380 respondents , the results show that self-regulation learning affects academic integrity with religiosity as a moderator variable of 54.2 % . Based on the results obtained, it shows that the effect of self-regulated learning on academic integrity in students is in the form of a positive relationship, meaning that the higher the level of self-regulated learning in students, the higher the level of academic integrity . Religiosity as a moderator variable in this study illustrates that it can strengthen the influence of self- regulated learning variables on student academic integrity.